Broadband bimorph piezoelectric energy harvesting by exploiting bending-torsion of L-shaped structure. (15th February 2020) - Li, Haisheng; Liu, Donghuan; Wang, Jianjun; Shang, Xinchun; Hajj, Muhammad R.
Highlights: Face extension and shear modes are exploited to expand the bandwidth and increase the level of harvested energy. The L-shaped harvester is a promising harvester that supports multi-directional and multi-modal energy harvesting. A model for a bimorph L-shaped harvester is presented and validated with simulations and experiments. Effect of key parameters on the energy harvesting efficiency are investigated. Abstract: Vibration-based piezoelectric energy harvesting has the potential to effectively power electronic sensors and communication devices of wireless networks. To address the need to increase the levels of harvested energy and increase its frequency bandwidth, we exploit multi-modal and multi-directional responses of a simple structure. Given advances made in developing piezoelectric materials with large face shear piezoelectric coefficients ( d 36 ), we explore the potential of developing a broadband and highly efficient bending-torsion L-shaped bimorph harvester through exploiting the d 31 and d 36 modes. A distributed-parameter model based on the Euler-Bernoulli beam assumptions is developed to assess the efficiency and power density of the proposed harvester. The model is validated with experiments and finite element simulations. The influence of the excitation angle as well as key geometric parameters of the L-shaped harvester on the energy harvesting efficiency and voltage frequency-response curve are presented and analyzed. The results show that the proposed structure and approach improves the frequency bandwidth with a frequency response that covers the first three modes of the harvester. The harvester yields an average power of 1.790 μW over a frequency range between 20 and 200 Hz, which is larger than bending mode L-shaped harvester (0.825 μW), cantilever harvester with the same length of main beam (0.764 μW) and auxiliary beam (1.037 μW). The investigated L-shaped structure constitutes a promising harvester that supports multi-directional and multi-mode energy harvesting.